Radio frequency transistors principles and practical applications - Dye, Norm, 1929-; Granberg, Helge, 1932- (Boston : Newnes, 2001)
Radio Frequency Transistors: Principles and Practical Applications is a complete tool kit for successful RF circuit design. As cellular and satellite communications fields continue to expand, the need for RF circuit design grows. Radio Frequency Transistors contains a wealth of practical design information based on years of experience from authors who have worked with the leading manufacturers of RF components. The book focuses primarily on the more difficult area of high power transistor amplifier design and construction.An entire chapter devoted solely to LDMOS high power RF transistors has.
Understanding RF data sheet parameters -- RF transistor fundamentals -- FETs and BJTs: comparison of parameters and circuitry -- Other factors affecting amplifier design -- Reliability considerations -- Construction techniques -- Power amplifier design -- Computer-aided design programs -- After the power amplifier -- Wideband impedance matching -- Power splitting and combining -- Frequency compensation and negative feedback -- Small signal amplifier design -- LDMOS RF power transistors and their applications.
Includes bibliographical references and index.
Keywords: Power transistors; Transistor amplifiers; Transistor radio transmitters; Amplifiers, Radio frequency; Electronic books